The Role Of Social Studies Teachers In Developing Students' Disciplined Learning Attitudes At Madrasah Aliyah Laboratory Of The State Islamic University Of North Sumatra Medan - Harahap, Dinda Tazkiyah; Endayani, Henni; Rachman, Fatur (Edumaniora : Jurnal Pendidikan dan Humaniora, 2024)
This study examines the role of social studies teachers in fostering students' learning discipline attitudes at Madrasah Aliyah Laboratorium UINSU Medan. The methodology of this study uses a qualitative research approach with a descriptive method. Data were collected through observation, interviews, and documentation. The subjects of the study consisted of 4 social studies teachers, 5 students of class X MA Laboratorium UINSU Medan and WKM in the student affairs field. The results of the study showed the role of social studies teachers who can foster students' learning discipline attitudes, namely social studies teachers have a role as mentors, social studies teachers have a role as motivators, social studies teachers have a role as demonstrator, social studies teachers have a role as facilitators, social studies teachers play a role as learning managers. In conclusion, the role of social studies teachers is very much needed in fostering students' learning discipline attitudes, therefore it is important for social studies teachers to carry out their roles well so that all students at Madrasah Aliyah Laboratorium UINSU Medan, especially class X students, can apply disciplined attitudes in learning when at school.